Inter-Pregnancy Interval and the Incidence of Preterm Birth - Maryam Asgharnia; Tahereh Varasteh; Davoud Pourmarzi (Tehran University of Medical Sciences, 2020)
Objective: Preterm birth is associated with high rates of neonatal morbidity and mortality. This study aimed to investigate the relationship between inter-pregnancy interval and the incidence of preterm birth. Materials and methods: In a case-control study, 185 women with preterm delivery and 185 women with term delivery were included. Data including inter-pregnancy interval, demographic characteristics, history of prenatal and neonatal complications, parity, gravidity, type of delivery, and smoking status were collected. Results: The mean of the inter-pregnancy interval in the case and control groups were 79.84 ± 45.55 months and 78.49 ± 41.29 months, respectively (P = 0.767). Inter-pregnancy interval 12-month or less in comparison with Inter-pregnancy interval more than 24 months significantly increased the odds of preterm delivery (OR: 4.05, 95% CI: 1.06-15.39, p = 0.040). However, inter-pregnancy interval of 13-24 months was not a risk factor when compared with more than 24-month inter-pregnancy interval (OR: 1.54, 95% CI: 0.62-3.80, p = 0.351). Having an educational level less than high school in comparison with tertiary level decreased the odds of preterm delivery (OR: 0.25, 95% CI: 0.11-0.56, P = 0.040). With each increase in number of gravidity odds of preterm delivery increased by 1.5 times (95% CI: 1.11-2.04, P = 0.009). Having a history of preterm delivery (OR: 2.57, 95% CI: 1.17-5.64, P = 0.019) and experiencing preeclampsia (OR: 1.98, 95% CI: 1.06-3.68, P = 0.032) increased the odds of preterm delivery. Conclusion: Inter-pregnancy interval of 12-month or less in comparison with more than 2-year inter-pregnancy interval, experiencing preeclampsia, history of preterm delivery and increased number of gravidity increase the risk of preterm delivery. Health care providers need to be informed with the appropriate inter-pregnancy interval and counsel women to make an informed decision regarding their pregnancy.